Hepatocardiorenal Syndrome: Integrating Pathophysiology with Clinical Decision-Making via Point-Of-Care Ultrasound - Abhilash Koratala; Claudio Ronco; Amir Kazory (Cardiorenal Medicine)
Background: Accumulating evidence has challenged the traditional model of the liver-kidney connection in hepatorenal syndrome. Cirrhosis can significantly impact cardiac function, leading to cirrhotic cardiomyopathy. Recent understanding reveals how cardiac dysfunction plays a pivotal role in the development of renal dysfunction in this setting, suggesting that disturbances traditionally categorized under hepatorenal syndrome may actually represent a hepatic form of cardiorenal syndrome – hepatocardiorenal syndrome – where the liver affects the kidney through cardiorenal pathways. Summary: Effective management of hepatocardiorenal syndrome and acute kidney injury in cirrhosis relies on accurately assessing a patient’s hemodynamic and volume status. Point-of-care ultrasound, including lung and focused cardiac ultrasound, is a valuable diagnostic tool that provides crucial data on fluid tolerance, subclinical pulmonary congestion, and left ventricular filling pressures. This objective, bedside approach offers a comprehensive assessment that directly influences patient management and therapeutic decisions. Key Messages: Point-of-care ultrasound plays an essential role in evaluating and managing hepatocardiorenal syndrome, providing insights into the underlying pathophysiology. By assessing hemodynamic parameters, it helps guide therapy and monitor patient responses, ensuring more accurate and effective treatment of patients with cirrhosis and acute kidney injury.